Perception of nurses from the maternal-child health services about signs of the beginning of childbirth work (Research, Society and Development, 2021)
Objectives: To identify the signs of labor onset, according to the professionals of the Cegonha network. Methodology: This is a cross-sectional study, with a primary data approach, carried out in units of the Rede Cegonha, from August 2017 to July 2019. The sample consisted of 84 nurses. Data collection was performed using variables of interest to the study. A descriptive statistic was performed, for all statistics the significance level of 5% was adopted. This research was approved under CAAE registration: 87854418.3.0000.5187. Results: regarding the signs of the beginning of labor, the following were mentioned: exit of the mucous plug, contractions that constantly increase its strength and pain that starts in the lumbar region and migrates to the pubis (47.94%, n = 35). Also cited were: uterine contractions with a different pattern from the current recommendations and vaginal losses (52.63%, n = 40); contractions, vaginal losses and dilation (10.52%, n = 8); contractions only (15.76%, n = 12). Conclusions: There is not only one sign or symptom that is definitive for the identification of the beginning of labor, but one must take into account the subjectivity and the multifactorial nature that involves care, recognizing each sign and symptom. It is necessary to improve the preparation for childbirth in order to collaborate for a better assistance.